The predictive relationship between the dimensions of academic support and academic burnout among undergraduate students in light of the use of distance learning - Boriek, Elsayed Ramadan (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to know the level of academic support and academic burnout among King Saud University students, in addition to determining the predictive relationship between the dimensions of academic support and academic burnout, The study sample consisted of (337) male and female students (252 males, 85 females), and the academic support scale and the academic burnout scale (prepared/researcher) were applied to them. The study ended with a set of results; Including: There are statistically significant differences at the level (α = 0.05) between the average degrees of academic support for students at King Saud University in the light of the use of distance learning according to the gender variable in favor of male students. And there were no statistically significant differences at the level (α = 0.05) between the average degrees of academic burnout among students at King Saud University in the light of the use of distance learning according to the variables of gender and academic specialization. The results also revealed the existence of an inverse linear relationship between academic support and academic burnout. Academic support explained (11%) of the discrepancy in academic burnout among King Saud University students.